Extracting and reshaping World Fertility Survey data in Stata - Germán Rodriguez; Trevor Croft (Demographic Research, 2017)
Background: The Demographic and Health Surveys (DHS) program has made available online a large number of public use files from its predecessor, the World Fertility Survey (WFS) program, see wfs.dhsprogram.com. Contribution: To encourage and facilitate the use of these data we provide a Stata command that can be used to extract and reshape the data, using local copies or directly from the DHS data archive pages.